2022
DOI: 10.1155/2022/2634431
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: A New Regulatory Mechanism in Osteoporosis

Abstract: Osteoporosis can be caused by a multitude of factors and is defined by a decrease in bone density and mass caused by the destruction of bone microstructure, resulting in increased bone brittleness. Thus, it is a systemic bone disease in which patients are prone to fracture. The role of ferroptosis in the pathogenesis of osteoporosis has become a topic of growing interest. In this review, we discuss the cell morphology, basic mechanisms of ferroptosis, the relationship between ferroptosis and osteoclasts and os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 100 publications
1
44
0
Order By: Relevance
“…Among the downstream target molecules of NRF2, we found that GPX4 and SLC7A11 are essential markers of ferroptosis as well. An increasing number of studies have recently revealed that ferroptosis is involved in the mechanisms underlying diabetic osteogenesis [ 65 ]. As a pattern of regulated cell death, ferroptosis is distinguished by intracellular iron overload and lipid ROS accumulation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the downstream target molecules of NRF2, we found that GPX4 and SLC7A11 are essential markers of ferroptosis as well. An increasing number of studies have recently revealed that ferroptosis is involved in the mechanisms underlying diabetic osteogenesis [ 65 ]. As a pattern of regulated cell death, ferroptosis is distinguished by intracellular iron overload and lipid ROS accumulation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prednisolone induces osteoblasts and osteocytes apoptosis leading to a reduction in bone formation [ 30 ]. It is well known that iron is an important risk factor for OP [ 31 , 32 ]. Iron overload can influence bone formation and remodeling affecting bone microarchitecture and inducing bone loss [ 33 , 34 ].…”
Section: Bone Metabolism and Physiopathology Of Osteoporosismentioning
confidence: 99%
“…With intramuscular injection of lentivirus expressing TFR1, skeletal muscle regeneration is enhanced and suppresses ferroptosis in different age groups of mice, thus preventing osteoporosis [ 91 ]. Liu et al further clarified the relationship between ferroptosis and osteoporosis through animal models of osteoporosis in vivo and cell models in vitro [ 92 ]. From the above research content, we have a better understanding of ferroptosis orchestrated with osteoporosis than before and can treat and prevent osteoporosis according to some targets.…”
Section: Ferroptosis In Bone-related Diseasesmentioning
confidence: 99%